Aspectos lingüisticos en la traducción de cuestonarios de salud (británicos y estadounidenses) - Nereida Congost Maestre (JoSTrans: The Journal of Specialised Translation)
The present article examines linguistic aspects of the translations of North American and English health care questionnaires into Spanish. Such instruments are increasingly used in clinical trials to determine the impact of medical intervention or treatment, and by public health researchers to assess the outcome of health care services. We will be discussing some examples of different health patient scales which have had or still have some problems regarding their translations into Spanish after their linguistic validation process. We are analysing some linguistic aspects on the lexical, semantic, and morphosyntactic levels of the sentence, such as the translation of polysemic words, colloquial expressions, word order, lexical repetition, level of formality, lexical register, false friends, the lexical and syntactical conciseness, multiple-choice gradation, and finally the question on abbreviations. All these issues have to be observed and taken into account when translating a questionnaire. With a few exceptions, all the instruments so far developed are in the English language and are intended for use in English-speaking countries. Therefore, health status measures developed for use in one country cannot be translated directly into another language without contextual adaptation. The article concludes that Spanish translated questionnaires still present deficiencies to be corrected. Further research into linguistic aspects of their translation needs therefore to be undertaken so that accurate equivalence is reached between the source questionnaires and their target versions.